Analysis of Little League Baseball Athletes' Energy Expenditure on Outfield and Infield Position Throwing Skills - Gano Sumarno; Wildan Alfia Nugroho; Mesa Rahmi Stephani (Universitas Pendidikan Indonesia, 2022)
This study aims to analyze the energy requirements of the throwing technique of Little League Baseball Athletes. The method used is a survey method with a cross-sectional study design. The research population is the Bandung City Little League Baseball athletes as many as 30 people with a total sampling technique. Energy expenditure of throwing technique was measured using Polar GPS Watch and Heart Rate Monitor. The results showed that the calories expended by male athletes were lower than the calories expended by female athletes in throwing skills. The conclusion of this study is that there are differences in energy expenditure in outfield and infield throwing skills. The implications of this research can be used as input for athletes, coaches, and parents in determining and carrying out training programs so that athletes can achieve optimal performance and achievement.